Культуральна соціологія: “сильна програма” досліджень смислів соціального життя - Танчер, В.; Скокова, Л. (Социология: теория, методы, маркетинг, 2009)
The trend of cultural sociology usually associated with the name of Jeffrey Alexander is highly influential in modern theoretical sociology. During two last decades, he is actively elaborating this ‘brand’ on theoretical and organizational levels of American sociology. So the aim of the article is to wholly clarify theoretical, methodological and organizational achievements of Alexander’s cultural sociology. The authors analyze theoretical evolution of Alexander’s thought on the way to fulfillment of the cultural sociology project, as well as inquire into the main per spectives of this approach. They underline the idea of cultural sociology as aimed at study of collective (inter-subjective) meanings that are based on the common moral principles, emotions and values and have a dominant impact on individuals and groups. Besides this task, they are intended to clarify an internal cultural architecture of social meaning by means of analysis of cultural codes, narratives and symbolic actions. The basic principles embodied in the ‘strong program’ of the cultural sociology – as a one opposed to the ‘weak program’ of traditional sociology are analyzed in the article. It is also noted that the typical element (focus) of this trend in modern sociology is an active role of social analysts in description (understanding) of the social process, as well as theoretical interpretation of social life.